Analysis of Slope Stability in the Coal Mining Area of KUD Sinamar Sakato, Jorong Sinamar, Nagari Sinamar, Asam Jujuhan, Dharmasraya, West Sumatera - Dimas Agung Hermawan.HL; Yoszi Mingsi Anaperta; Heri Prabowo; Sultan Muhammad Taufik (Departemen Teknik Pertambangan FT UNP, 2024)
KUD Sinamar Sakato conducts mining with open pit mining method, an open pit mining will always face the problem of slope stability, if the slope formed from the excavation is not considered properly, it can lead to potential landslides. Based on observation data, KUD Sinamar Sakato has a slope with a height of 78 metres and an angle of 78o, KUD Sinamar Sakato also does not have information about the physical and mechanical properties of the slope of the Mining Pit, making it difficult for companies to conduct geotechnical studies. Based on the analysis of safety factors using slide v 6.0 software using the Morgenstern-Price method, the slopes of KUD Sinamar Sakato are unsafe in saturated conditions which have FK of 1.095, so it is necessary to make improvements to the slope geometry, the improvements made are reducing the slope of the slope to 73o and the resulting saturated FK is 1.360, the slope is in a safe condition, then the second recommendation is to add a bench without changing the angle, where the bench is added at a height of 35 metres with a bench width of 4 metres, the saturated FK is 1.361, where the slope is in a safe condition.